2019
DOI: 10.31219/osf.io/cg354
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When Mere Action Versus Inaction Leads to Robust Preference Change

Abstract: Understanding the formation and modification of preferences is important for explaining human behavior across many domains. Here we examined when and how preferences for food items can be changed by linking mere action versus inaction to these items. In 7 preregistered experiments, participants were trained to consistently respond to certain food items (go items) and not respond to other items (no-go items) in a go/no-go training. Next, to assess preferences, they repeatedly chose between go and no-go items fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…Reduced choices for no-go foods are consistent with previous studies that have used both go/no-go and stop-signal task paradigms [25,[71][72][73]. For example, Chen et al [71] showed that following a single training session, participants were more likely to choose go foods than no-go foods up to one week later.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Reduced choices for no-go foods are consistent with previous studies that have used both go/no-go and stop-signal task paradigms [25,[71][72][73]. For example, Chen et al [71] showed that following a single training session, participants were more likely to choose go foods than no-go foods up to one week later.…”
Section: Discussionsupporting
confidence: 84%
“…Reduced choices for no-go foods are consistent with previous studies that have used both go/no-go and stop-signal task paradigms [25,[71][72][73]. For example, Chen et al [71] showed that following a single training session, participants were more likely to choose go foods than no-go foods up to one week later. Importantly, previous research has indicated that training effects on food choice may be mediated by the devaluation of no-go foods [25], although in this study, there was not conclusive evidence for a no-go devaluation effect as discussed further below (also see review by Veling et al [29]).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Fourth, food choice. Snack items associated with ‘no-go’ cues were chosen less following training compared to snack items associated with ‘go’ cues [61,62]. Chen et al [61] also showed that the probability of choosing a healthful food (fruit or vegetable) over an unhealthy food (crisps and candy bars) could be increased by associating healthy foods with ‘go’ cues and unhealthy foods with ‘no-go’ cues.…”
Section: Cognitive Training To Help Modify Food-related Choices: a Nementioning
confidence: 99%